Analisis Dinamika Kelimpahan Spirulina SP. Pada Tambak Udang Vaname (L. Vannamei) Pola Intensif - Ariadi, Heri; Fahrurrozi, Ashari; Al Ramadhani, Farchan Mushaf (Universitas Pahlawan Tuanku Tambusai, 2024)
Spirulina sp. is a type of plankton commonly found in pond waters. The purpose of this study is to detect the abundance of plankton and the presence of Spirulina sp. in the pond waters used for cultivating vannamei shrimp (L. vannamei). The research methods employed are descriptive quantitative and qualitative analyses, complemented by dynamic system modeling analysis. The results indicate that the water quality conditions of the ponds are still suitable for shrimp farming, with dissolved oxygen levels ranging from 4.01 to 6.17 mg/L, pH levels from 7.7 to 7.9, salinity at 20‰, temperature ranging from 27.050 to 28.25°C, nitrate levels from 0.01 to 0.15 mg/L, phosphate levels from 0.05 to 0.20 mg/L, and water clarity between 25 and 35 cm. The plankton classification identified includes the class Bacillariophyceae with genera such as Skeletonema sp., Cyclotella sp., Coscinodiscus sp., and Amphipora sp.; the class Chlorophyceae with genera such as Chlorella sp., Oocystis sp., and Chlamydomonas sp.; and the class Cyanophyceae with genera such as Oscillatoria sp., Spirulina sp., and Anabaenopsis sp. The plankton diversity index (H’) ranged from 0.01 to 0.33, and the evenness index (E) ranged from 0.10 to 0.50, indicating that the pond waters are still in relatively good condition with minimal indications of pollution. The abundance of Spirulina sp. ranged from 0.2x10^4 to 0.6x10^4 cells/ml. The dynamic system modeling analysis showed that the abundance of Spirulina sp. in pond waters is influenced by the productivity levels of the waters and the grazing process by organisms. In conclusion, the abundance of plankton found in the ponds ranges from 0.4x10^4 to 1.9x10^4 cells/ml, consisting of 10 genera and 3 classes of plankton. Additionally, Spirulina sp. was found in all three research ponds, with an abundance ranging from 0.2x10^4 to 0.6x10^4 cells/ml.